A love story from the end of the world : stories - Kim, Juhea (Ecco, 2025)
"From the acclaimed author of Beasts of a Little Land and City of Night Birds, an exquisite, globetrotting story collection about humans in precarious balance with the natural world. Spanning multiple locales and epochs, and rendered in fine detail and vivid color, this transportive collection shows what it means to live as human inhabitants on our one miraculous planet. Lyrical, at times hilarious, and always heartfelt, each of these ten stories is a reflection of individual choice in the face of man-made apocalypse: in a near-future Seoul, where air pollution has become so fatal that the city has been encased in a translucent biodome, a civil engineer charged with its upkeep contemplates an arranged marriage. A painter, disenchanted with New York City, travels to the South of France and falls into a dalliance with an entrepreneur who claims to have invented a new color. And on an island where the Indian and Pacific Oceans meet, upon which other countries have relegated their waste to form a mountain of landfill, a local boy facing daily privation gets internet famous for his K-pop-inspired dances. With the clear-eyed reverence of Richard Powers and the sparkling sincerity of George Saunders, Juhea Kim's first story collection views our broken world-and broken hearts-from breathtaking heights. A Love Story from the End of the World delivers an impassioned reminder that we are human-but without nature, we are nothing at all"-- Provided by publisher.